INHIBITORY EFFECT OF EMODIN ON RAW 264.7 ACTIVATED WITH DOUBLE STRANDED RNA ANALOGUE POLY I:C - Kim, Young-Jin; Lee, Ji Young; Kim, Hyun-Ju; Kim, Do-Hoon; Lee, Tae Hee; Kang, Mi Suk; Choi, You- Kyung; Lee, Hye Lim; Kim, Jaieun; An, Hyo-Jin; Park, Wansu (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Emodin (3-methyl-1, 6, 8-trihydroxyanthraquinone) is a compound which can be found in PolygoniMultiflori Radix (PMR). PMR is the root of Polygonum multiflorum. PMR is used to treat dizziness, spermatorrhea,sores, and scrofula as well as chronic malaria traditionally in China and Korea. The anti-tumor property of emodin wasalready reported. However, anti-viral activity of emodin on macrophages are not fully reported.Materials and Methods: Effects of emodin on RAW 264.7 mouse macrophages induced by polyinosinic-polycytidylicacid (poly I:C), a synthetic analog of double-stranded RNA, were evaluated.Results: Emodin restored the cell viability in poly I:C-induced RAW 264.7 at concentrations of up to 50 μM. Emodinsignificantly inhibited the production of nitric oxide, IL-1α, IL-1β, IL-6, GM-CSF, G-CSF, M-CSF, MCP-1, MIP-1α,MIP-1β, MIP-2, RANTES, and IP-10 as well as calcium release and mRNA expression of signal transducer andactivated transcription 1 (STAT1) in poly I:C-induced RAW 264.7 (P < 0.05).Conclusion: This study shows the inhibitory effect of emodin on poly I:C-induced RAW 264.7 via calcium-STATpathway.